Sustainable Business Model Development of Salam Rancage Bogor Using Triple Layered Business Model Canvas - Fadila, Rinda; Asnawi, Yudha Heryawan; Taryana, Asep (School of Business, IPB University (SB-IPB), 2024)
The Business Model Canvas (BMC) is a tool commonly used by companies to create business models. However, the weakness of BMC is still focused on increasing profits and ignoring other sustainability concepts. The research focuses on the use of the Triple Layered Business Model Canvas (TLBMC) to create business models focused on sustainability issues on SME scale. This research was conducted at a social enterprise in Bogor named Salam Rancage from December 2022-February 2023. The primary data was collected by field observations and in-depth interviews with management, artisans, and an old customer. Secondary data include internal documents, previous research, scientific journals, and data from the internet. The data is analyzed using descriptive analysis techniques and by mapping the 27 elements of TLBMC. The results of the study show that the application of the TLBMC framework in Salam Rancage can be implemented in significantly covering three aspects of economic, environmental, and social issues that have not been covered in the BMC framework. The TLBMC framework is one of the tools that can be considered to achieve more sustainable business. Keywords: model business, salam rancage, social enterprise, sustainability, TLBMC